Classification and Disposal Strategy of Excess Sludge in the Petrochemical Industry - Lei Guo; Hongzhe Zhang; Xueyan Jiang; Yan Wang; Zhengwei Liu; Shiping Fang; Zhiyuan Zhang (Applied Sciences, 2019)
The excess sludge in the petrochemical industry is large in quantity, complex in composition, and highly harmful, and its rational disposal is of great significance for environmental protection and sustainable development. In the present study, a classification and disposal strategy for the excess sludge in the petrochemical industry is proposed. The strategy first analyzes the dioxin, flammability, corrosivity, reactivity, and leaching properties of the sludge, from which the waste type of the sludge (general waste or hazardous waste) can be determined. Then, methods of disposal can be selected depending on the type of waste and the corresponding risk analysis, enabling rationalized disposal of the sludge. To verify the effectiveness and practicability of the proposed sludge classification and disposal strategy, research on petrochemical excess sludge samples (i.e., Ah, Bl, and Cq) originated from three different regions in China is carried out as a case study. The component analysis of the above three sludge samples revealed that they are all general wastes. In addition, the possibility of employing Cq sludge for landfill, soil modification, and greening mud, as well as the risk of landfill and incineration disposal in solid waste landfills are investigated. Furthermore, natural radioactive elements uranium and thorium in Cq sludge sample are studied. The results show that Cq sludge cannot be used for landfill, soil modification, and greening mud due to excessive arsenic content. The proposed strategy provides a basis for the selection of reasonable petrochemical excess sludge disposal methods.